Immobilization of antimicrobial peptides from Lactobacillus sakei subsp. sakei 2a in bacterial cellulose: structural and functional stabilization - Malheiros, Patrícia S. (2018)
Lactobacillus sakei subsp. sakei 2a is a bacteriocinogenic lactic acid bacterium isolated from Brazilian pork sausage, which produces antimicrobial peptides (bacteriocins) able to control the growth of important foodborne pathogens. These antimicrobial peptides were immobilized by physical entrapment in bacterial cellulose (BC) membranes produced by Gluconacetobacter xylinus, aiming at improving their antimicrobial activity against Listeria monocytogenes. Scanning Electron Microscopy indicated the BC membranes presented an entangled structure, with void spaces ramndomly distributed throughout the membrane matrix, facilitating the entrappment and immobilization of the bacteriocins. Both free and BC membrane entrapped bacteriocins were applied to an artificial bacterial lawn of Listeria monocytogenes grown on solid BHI medium, and incubated at either room (30°C) or refrigerated (7°C) temperatures during 24h or 7d, respectively. At room temperature, the bacteriocins entrapped within BC membranes were significantly (p<0.05) more efficient in the control of pathogen growth when compared to the free bacteriocins, during the whole timeframe under study. At refrigeration temperature, both free and entrapped bacteriocins led to inactivation of the pathogen after 5 days. These results are good evidence that entrapment of bacteriocins produced by Lb. sakei 2a in BC membranes is as a promising strategy for the control of L. monocytogenes in foods.